Fire‐stimulated reproduction in the resprouting, non‐serotinous conifer Podocarpus drouynianus (Podocarpaceae): the impact of a changing fire regime. Issue 1 (16th September 2015) - Nield, Andrew P.; Enright, Neal J.; Ladd, Philip G.
Abstract: Species with fire stimulated reproduction (fsr) are common in Mediterranean climate ecosystems. We investigated how season of, and time since, fire affects seed production in Podocarpus drouynianus F. Muell., a dioecious resprouting coniferous shrub endemic to the jarrah ( Eucalyptus marginata Sm.) forests of southwestern Australia, and if the now largely managed fire regime in these forests poses a risk to its persistence. We hypothesised that, like other species showing fsr, seed production in P. drouynianus would be limited to the first few years following fire and seed set would be lower after spring burns. Mature plants regenerated rapidly from buried stem tissue (lignotuber) after fire, producing abundant sporophylls in autumn 12–18 months later. Stands burnt in autumn showed peak seed production 1 year later, while for those burned in spring, peak seed production was delayed until the second autumn after fire. Limited seed production occurred for up to 3 years following fire, but no seed production was observed in longer unburnt (>10 years since fire) stands. While we did not observe a significant impact of fire season on seed production, seed weight and viability were lower for spring‐burnt plants. Population‐level effects associated with plant density may also have negative impacts on P. drouynianus demography, with females within a small population burnt in autumn producing very few seeds 12 months following fire. Interactions between climate change, fire regimes and fire management practices need to be considered in order to best safeguard the long‐term persistence of this conifer species.